ION CHROMATOGRAPHY METHOD FOR DETERMINATION OF ISOPROPYLAMINE CONTENT IN METOPROLOL SUCCINATE - More, Rohan; Gosar, Dr. Amit; Shaikh, Dr. Tabrez; Joglekar, Amit (Journal of Biomedical and Pharmaceutical Research, 2019)
A simple, sensitive, specific, linear and effective Ion chromatography method has been developed and validated for the determination of Isopropylamine content in Metoprolol Succinate. Isopropylamine is possible impurity that may be present in Metoprolol succinate samples. The method was validated as per International Council for Harmonisation (ICH) guidelines, for which limit of detection and limit of quantitation obtained were 29 ppm and 87 ppm respectively. % RSD for System precision observed was 1.38. The regression coefficient found for the linearity study was 0.9997. The % recovery of the spiked Isopropylamine in drug substance obtained was in the range of 83.2 to 100.7 from 50 % to 150 % level ensured the accuracy of the method. The method can be adapted to determine Isopropylamine content in Metoprolol Succinate drug substance (API). Keywords: Ion chromatography (IC), Metoprolol Succinate, Isopropylamine, development, validation.